Comprehensive Evaluation of Biological Fresh Weight Yield-related Characteristics of Silage Maize (Zea mays) at Maturity Stage - Yun Yang; Shuanglin Mao; Shiwei Li; Yun Long; Chuan He; Qingqing Xia; Rong Jin; Peng Wang; Peng Fu; Quanbo Pu (BioResources, 2025)
Biological yield and quality are critical indicators for evaluating silage corn (Zea mays). Among these, biological yield is closely associated with multiple traits of the crop. This study recorded data of 10 traits over two years for 37 silage corn varieties cultivated in hilly mountainous regions of China. Multivariate analysis revealed correlations among all 10 traits. Using correlation data, principal component analysis, cluster analysis, and ridge regression were applied to classify the 37 silage corn varieties into six distinct groups. Key findings identified plant height, ear height, greenness retention rate, and dry weight as critical variables for developing a mathematical model to evaluate silage corn yield and estimate its biological fresh weight. Results indicated that when screening for high-biological-fresh-weight silage corn varieties, priority should be given to those with longer growing periods, compact plant types, superior greenness retention, and higher dry weight. Finally, comparative analysis of biological yields of high-yielding silage corn in Sichuan Province, China, provided actionable references for optimizing silage corn cultivation in local hilly regions.